2020
DOI: 10.1177/0022057420903269
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Video Annotation Tools and Informal Online Discussions to Explore Preservice Teachers’ Self- and Peer-Evaluation of Academic Feedback

Abstract: This study explored the quality of preservice teachers’ self- and peer-academic feedback using video annotation tools to capture their teaching practices. They were also provided with an informal online discussion board as part of the peer support system. Twenty-five preservice teachers at a large university in the Southwestern United States volunteered to participate in this study. Data revealed a striking difference between self-evaluation and peer-evaluation. Preservice teachers rated themselves considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
1
1
Order By: Relevance
“…They could have more time to consider their ideas and critiques more thoroughly before providing feedback. However, it is in contrast with one study which found that even when the feedback was specific, it ended up just being a narration what happened in the video without critical analysis or lacks specificity (Zaier et al, 2020).…”
Section: Learning Values In Technology-supported Peer Feedbackcontrasting
confidence: 57%
“…They could have more time to consider their ideas and critiques more thoroughly before providing feedback. However, it is in contrast with one study which found that even when the feedback was specific, it ended up just being a narration what happened in the video without critical analysis or lacks specificity (Zaier et al, 2020).…”
Section: Learning Values In Technology-supported Peer Feedbackcontrasting
confidence: 57%
“…Interessen for nyere feedback-formater og multimodale feedback-teknologier er dog stigende i takt med at flere lettilgaengelige feedback-redskaber som screencast, chat, padlets m.fl. begynder at dukke op (fx Fang et al, 2021;Cutting & Larkin, 2021;Zaier et al, 2021). Det gaelder for skriftlige såvel som mundtlige feedback-former.…”
Section: Feedback Som Digital Laeringsaktivitetunclassified
“…The most widely cited article, (Rich & Hannafin, 2009 ), provides many detailed discussions about different uses of video annotation in teaching and learning. However, more recently, studies such as Zaier et al ( 2020 ) and Cattaneo et al, 2020 continue to argue for video annotation’s ability to facilitate peer evaluation, academic feedback, and self-evaluation. In behavior analysis, Mirriahi et al ( 2016 ) investigated cluster diagrams of video annotation behavior and determined that viewers reflected one of four behavior types: minimalist, disenchanted, task-focused, or intensive group clusters.…”
Section: Previous Literaturementioning
confidence: 99%